Semi-active suspension system simulation using Simulink. (3rd August 2009) - Abramov, Sergey; Mannan, Samjid; Durieux, Olivier
This paper describes a simulation design procedure aimed to achieve improved performance of the vehicle semi-active suspension. The issues related to the design of vehicle models with skyhook control are discussed. Three basic models with linear parameters are explained: quarter-, half- and full-car. The road profile is generated from a spatial power spectral density (PSD) to represent a typical road (based on ISO 8608 classification). The normalised root-mean-square values of sprung mass acceleration and tyre load forces are used to assess the vehicle ride comfort and handling performance based on five benchmark road profiles employed in industrial tests.